1993
DOI: 10.1192/bjp.163.6.755
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem in Recovered Bipolar and Unipolar Out-patients

Abstract: The hypothesis of a low self-esteem in depressive patients was tested using the Rosenberg Self-Esteem Scale in 24 recovered unipolar and 27 recovered bipolar patients, compared with a normal control group of 26 subjects matched for age and sex. The hypothesis was confirmed only for unipolars; bipolar patients presented a self-esteem score not significantly different from normal scores. Self-esteem was not related to clinical characteristics of the affective disorder, suggesting that low self-esteem may be a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 40 publications
6
26
0
3
Order By: Relevance
“…The findings relevant to self-esteem are in line with previous studies in which the self-esteem of UP patients during remission was consistently found to be lower in comparison to that of controls [8,16,17]. For BP disorder, patients' self-esteem was not different than that of controls in one study [8], but was lower in two other studies [16,17].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The findings relevant to self-esteem are in line with previous studies in which the self-esteem of UP patients during remission was consistently found to be lower in comparison to that of controls [8,16,17]. For BP disorder, patients' self-esteem was not different than that of controls in one study [8], but was lower in two other studies [16,17].…”
Section: Discussionsupporting
confidence: 89%
“…Population differences among studies may explain the discrepancies regarding self-esteem in BP patients, since it has been supported that the concept of self-esteem is under strong cultural influence [38]. Indeed, the studies with the positive findings were conducted on Italian and Jewish populations [16,17], while the negative results referred to Belgian [8] and Greek subjects in the present study. Self-esteem in UP patients, in contrast, seems to be independent of the origin of the sample.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations